2017
DOI: 10.1097/aln.0000000000001571
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induces Internalization of κ-Opioid Receptor

Abstract: Background It has been demonstrated that κ-opioid receptor agonists can reduce hypoxia–ischemia brain injury in animal models. However, it is unclear how the κ-opioid receptor responds to hypoxia–ischemia. In the current study, the authors used an in vitro model of oxygen–glucose deprivation and reoxygenation to explore how κ-opioid receptors respond to hypoxia and reoxygenation. Methods Mouse neuroblastoma Neuro2A cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…17 KOR-related cerebral I/H injury studies showed 4 h OGD can damage KOR recirculation, reducing the total number of KOR and leading to receptor downregulation. 18 Our study found that both MOR inhibitor F I G U R E 2 Effects of Herkinorin and MOR inhibitor, β-funaltrexamine on NLRP3 inflammasome in rat primary neurons exposed to OGD/R. (A) The typical Western blot results showed the changes in the expression of pro-IL1β, IL-1β, pro-Caspase1, Caspase1 p20, and NLRP3 in rat primary neurons.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…17 KOR-related cerebral I/H injury studies showed 4 h OGD can damage KOR recirculation, reducing the total number of KOR and leading to receptor downregulation. 18 Our study found that both MOR inhibitor F I G U R E 2 Effects of Herkinorin and MOR inhibitor, β-funaltrexamine on NLRP3 inflammasome in rat primary neurons exposed to OGD/R. (A) The typical Western blot results showed the changes in the expression of pro-IL1β, IL-1β, pro-Caspase1, Caspase1 p20, and NLRP3 in rat primary neurons.…”
Section: Discussionmentioning
confidence: 83%
“…It was also found that the delayed brain protective effect of morphine was found in hippocampal slices, and was caused by the activation of MOR 17 . KOR‐related cerebral I/H injury studies showed 4 h OGD can damage KOR recirculation, reducing the total number of KOR and leading to receptor downregulation 18 . Our study found that both MOR inhibitor and MOR knockdown reversed the effects of Herkinorin downregulating NLRP3 to alleviate cerebral ischemic injury, suggesting that MOR plays an important role in Herkinorin neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro hypoxia may also be studied to uncover the molecular mechanisms ameliorating ischemia/reperfusion injury in neurons (118) or cardiomyocytes (119). A perfusion-based model of murine cardiomyocytes subjected to abrupt anoxia and reperfusion was discovered to be an optimal platform for demonstrating the opening of mitochondrial permeability transition pores (mPTP).…”
Section: Sustained Hypoxiamentioning
confidence: 99%
“…Hypoxic tumor cells secrete VEGF and lactate, as well as a number of cytokines that modulate the tumor microenvironment, which increases their viability ( 160 , 161 ). The expression levels of KOR and hypoxia-inducible factor 1α (HIF-1α) are significantly increased in live human neurons following 24-h hypoxia ( 162 ). HIF-1α knockdown decreases KOR expression ( 162 ).…”
Section: Potential Roles Of Kor In Cancermentioning
confidence: 99%
“…The expression levels of KOR and hypoxia-inducible factor 1α (HIF-1α) are significantly increased in live human neurons following 24-h hypoxia ( 162 ). HIF-1α knockdown decreases KOR expression ( 162 ). Thus, during hypoxia, KOR promotes cell viability and its expression may be regulated by HIF-1α ( 163 ).…”
Section: Potential Roles Of Kor In Cancermentioning
confidence: 99%